EVALUATION OF FAMOTIDINE LOADED 3D-NANO-CELLULOSE NETWORK USED FOR ORAL ADMINISTRATION - MAI, VAN-HUNG; NGUYEN, XUAN-THANH; PHUNG, THI-KIM-HUE; L. E., THI-PHUONG (International Journal of Applied Pharmaceutics, 2020)
Objective: Evaluation Of Famotidine Loaded 3D-Nano-Cellulose Network three dimensional nano-cellulose network (3DNC) Used For Oral Administration. 3DNC is produced from bacteria living in fermented green tea and is the material containing nano-sized fibers, which is capable of loading Famotidine to form a prolonged release therapy to improve drug bioavailability. Methods: Used healthy white rabbits, weight approximately 2.5-2.7 kg, the same age, laboratory standard, is supplied from The National Institute of Drug Quality Control. The rabbits have adapted to laboratory conditions at least one week and have starveling in 12 h, supplied fully water during the preparation. Rabbits are divided into 4 groups (n=3 for each group). Every rabbit is given 1 capsule or 1 tablet with a single dose of 20 mg/rabbit: group 1 (commercial drugs), group 2 (3DNC-standard medium (SM) loaded drug), group 3 (3DNC-coconut medium (CM) loaded drug) Group 4 (3DNC-rice medium (RM) loaded drug). Results: The results have shown that 3DNC has the involvement of the nano-sized cellulose fibers with three-dimensional networks that are capable of loading Famotidine and prolonged drug release. The 3DNC cultured in the drug-loaded SM with slow-release and slow-release catalysts, the 3DNC was cultured in CMs and tablets with medium release rates, in comparison with the 3DNC was cultured in RM loaded at a rapid release rate in the same pH = 2. Conclusion: Experiment on rabbits showed that the drug-loaded 3DNCs could help to prolong the drug release, in which the extended-release time of the 3DNC cultured in SM and CM was higher than that of the 3DNC grown in RM. The 3DNC loaded drugs help improve Famotidine bioavailability compared to commercial tablets.